PERILAKU IBU DALAM PENERAPAN TEKNIK MASSASE PADA BAYI USIA 2-12 BULAN - Murniwati Laia; Debora Paninsari; Saskia Sitindoan; Shanty Satria; Sintia Mutiara Yohana; Sinur Hanna Putri (Jurnal Ilmiah Citra Kebidanan, 2025)
Infant massage is a form of health care that involves touch therapy by applying certain techniques. This therapy aims to provide touch stimulation that supports infant health. The design of this study uses a descriptive type with a quantitative method that aims to determine maternal behavior in applying massage techniques to infants. This study took a population of mothers who had babies aged 2-12 months as many as 38 people. The simple random sampling method was used to determine the research sample of 35 people. The variables in this study were maternal behavior in applying massage techniques to infants. The study used a questionnaire of 10 positive and negative statements as an instrument covering the parameters of maternal knowledge, actions and attitudes. The study processed data by Editing, Coding, Scoring. Based on this study, it was found that maternal behavior in applying massage techniques to infants, there were 13 respondents (34.3%) who had sufficient behavior, 12 respondents (34.1%) had good behavior and 10 respondents (28.6%) had poor behavior. In conclusion, there is still a lack of maternal behavior in applying massage techniques to infants.